The effect of social support, gratitude, resilience and satisfaction with life on depressive symptoms among police officers following Hurricane Katrina - McCanlies, Erin C (Int J Soc Psychiatry, 2018)
BACKGROUND: Police officers in the New Orleans geographic area faced a number of challenges following Hurricane Katrina. AIM: This cross-sectional study examined the effect of social support, gratitude, resilience and satisfaction with life on symptoms of depression. METHOD: A total of 86 male and 30 female police officers from Louisiana participated in this study. Ordinary least-square (OLS) regression mediation analysis was used to estimate direct and indirect effects between social support, gratitude, resilience, satisfaction with life and symptoms of depression. All models were adjusted for age, alcohol intake, military experience and an increase in the number of sick days since Hurricane Katrina. RESULTS: Mean depressive symptom scores were 9.6 ± 9.1 for females and 10.9 ± 9.6 for males. Mediation analyses indicates that social support and gratitude are directly associated with fewer symptoms of depression. Social support also mediated the relationships between gratitude and depression, gratitude and satisfaction with life, and satisfaction with life and depression. Similarly, resilience mediated the relationship between social support and fewer symptoms of depression. CONCLUSION: Social support, gratitude and resilience are associated with higher satisfaction with life and fewer symptoms of depression. Targeting and building these factors may improve an officer’s ability to address symptoms of depression.